2016
DOI: 10.17305/bjbms.2016.1245
|View full text |Cite
|
Sign up to set email alerts
|

Combination effect of cytochrome P450 1A1 gene polymorphisms on uterine leiomyoma: A case-control study

Abstract: Uterine leiomyoma (UL) is an estrogen-dependent neoplasm of the uterus, and estrogen metabolizing enzymes affect its progression. This study aimed to evaluate the association between two single-nucleotide polymorphisms of cytochrome P450 1A1 (CYP1A1) gene and UL risk. The study consisted of 105 patients with UL and 112 healthy women as controls. Ile462Val (A/G) and Asp449Asp (T/C) polymorphisms of CYP1A1 gene were analyzed by DNA sequencing and polymerase chain reaction-restriction fragment length polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Ye et al (2018) 1 proved that there is a risk relationship between uterine leiomyoma and CYP1A1 gene polymorphism, this is the same as the study results obtained by Herr, et al (2006). 6 who stated that the polymorphism of the cytochrome P450 1A1 gene in uterine leiomyomas has nothing to do with the polymorphism of the CYP1A1 gene. Based on the previous research, it is known that there is a relationship between GEN CYP1A1 (Ile462Val) and leiomyoma uteri, therefore it is necessary to study the relationship between CYP1A1 gene polymorphism (Ile462Val) and uterine myoma in Malays ethnicity in Indonesia, especially in South Sumatera, which is Indonesia's occupied territory.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Ye et al (2018) 1 proved that there is a risk relationship between uterine leiomyoma and CYP1A1 gene polymorphism, this is the same as the study results obtained by Herr, et al (2006). 6 who stated that the polymorphism of the cytochrome P450 1A1 gene in uterine leiomyomas has nothing to do with the polymorphism of the CYP1A1 gene. Based on the previous research, it is known that there is a relationship between GEN CYP1A1 (Ile462Val) and leiomyoma uteri, therefore it is necessary to study the relationship between CYP1A1 gene polymorphism (Ile462Val) and uterine myoma in Malays ethnicity in Indonesia, especially in South Sumatera, which is Indonesia's occupied territory.…”
Section: Introductionmentioning
confidence: 53%
“…5 Uterine myomas as common benign neoplasms of the uterus involve nearly 30-40% of women childbearing age. 6 Myoma uteri originates from the smooth muscle of the uterus and develops from stimulation of the hormone estrogen. The development of uterine myomas depends on estrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Cytochrome P4501A1 ( CYP1A1 ) is a member of the cytochrome P450 gene family located on chromosome 15, is one of the most important phases I enzymes, and plays an important role in the metabolism of exogenous and endogenous material. In recent research, it has been shown that there have been variants of rs1048943 within the cytochrome P4501A1 ( CYP1A1 ) gene, which have been associated with smooth muscle tumor of the uterus, chronic obstructive pulmonary disease and esophageal cancer and other diseases.…”
Section: Introductionmentioning
confidence: 99%